2018
DOI: 10.15252/embr.201744742
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the molecular determinants for Cenp‐F localization to nuclear pores and kinetochores

Abstract: Cenp-F is a multifaceted protein implicated in cancer and developmental pathologies. The Cenp-F C-terminal region contains overlapping binding sites for numerous proteins that contribute to its functions throughout the cell cycle. Here, we focus on the nuclear pore protein Nup133 that interacts with Cenp-F both at nuclear pores in prophase and at kinetochores in mitosis, and on the kinase Bub1, known to contribute to Cenp-F targeting to kinetochores. By combining structural modeling and yeast two-hybrid assays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 66 publications
6
41
0
Order By: Relevance
“…Our identification of a minimal kinetochore-targeting domain of HsCENP-F within residues 2922-2990 agrees with a previous study that made use of CENP-F deletion mutants (Zhu, 1999). It also agrees with another study, currently in press, that identified distinct binding domains in CENP-F for nuclear envelope and for kinetochore localization (Berto et al, 2018). Specifically, residues 2655 to 2860 of mouse CENP-F (corresponding to residues 2866-3072 of HsCENP-F) were sufficient for kinetochore recruitment (Berto et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our identification of a minimal kinetochore-targeting domain of HsCENP-F within residues 2922-2990 agrees with a previous study that made use of CENP-F deletion mutants (Zhu, 1999). It also agrees with another study, currently in press, that identified distinct binding domains in CENP-F for nuclear envelope and for kinetochore localization (Berto et al, 2018). Specifically, residues 2655 to 2860 of mouse CENP-F (corresponding to residues 2866-3072 of HsCENP-F) were sufficient for kinetochore recruitment (Berto et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…The role of Bub1 in CENP-F kinetochore recruitment was already established in previous work (Berto et al, 2018; Johnson et al, 2004; Liu et al, 2006; Raaijmakers et al, 2018), and a very recent study implicated the Bub1 kinase domain in CENP-F kinetochore recruitment (Raaijmakers et al, 2018). Here, we have extended this previous study by showing that the interaction of the Bub1 kinase domain and CENP-F is direct, and by identifying a minimal CENP-F domain involved in this interaction and capable of kinetochore localization.…”
Section: Discussionmentioning
confidence: 69%
“…CENP-F is an enigmatic protein with a plethora of suggested cellular functions ranging from chromosome segregation to mitochondrial trafficking. Because of the number of its binding partners and involvement in different cellular processes, a careful genetic dissection is needed to study specific roles of CENP-F. Variants of CENP-F have been characterized that separate its functions at the nuclear envelope and kinetochores (Berto et al, 2018;Zhu, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently in prometaphase, CENP-F relocates to kinetochores (Rattner et al, 1993). The molecular mechanism of CENP-F kinetochore binding has been studied in great detail (Berto et al, 2018;Ciossani et al, 2018;Zhu, 1999). CENP-F is targeted to the outer kinetochore via a KT-core domain (residues 2792 to 2887, Fig 1A) via synergistic action of Bub1 kinase and the kinesin Cenp-E (Berto et al, 2018;Zhu, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, mutations affecting the kinetochore protein Cenp-F, an established partner of Nup133 49 were identified in patients affected by severe ciliopathy and microcephaly 50 .…”
Section: Discussionmentioning
confidence: 99%